Antecedents of Willingness to Recommend and Revisit Intention among International Golf Tourists in Thailand - Phetbuasak, Weerayudth; Nakornkhet, Kasem (Rajapark Journal, 2024)
This research aims to: 1) develop a causal relationship model of the antecedents of willingness to recommend and revisit intention among international golf tourists in Thailand, and 2) validate the consistency of this causal relationship model with empirical data. The study sampled 556 international tourists who traveled to play golf in Thailand, recruited through quota sampling methodology. Questionnaires were used as the primary instrument for data collection. The data analysis employed descriptive statistics (including frequency distribution, percentages, means, and standard deviations) and inferential statistics (specifically structural equation modeling). The empirical investigation revealed several significant findings: 1.1) Golf course accessibility, golf course management, perceived value, and country image had positive influences on memorable experiences at a statistical significance level of .01; 1.2) These factors mentioned above, together with memorable experiences, demonstrated statistically significant positive influences on golfer satisfaction at the .01 level; 1.3) Furthermore, both memorable experiences and golfer satisfaction exhibited statistically significant positive effects on willingness to recommend at the .01 level; 1.4) In a similar vein, memorable experiences and golfer satisfaction showed statistically significant positive impacts on revisit intention for golf-related purposes at the .01 level; and 2) The causal relationship model of the antecedents of willingness to recommend and revisit intention for golf was consistent with the empirical data. The key fit indices met their respective criteria: χ²/df = 1.081 (< 2), p = 0.098 (> .05), RMSEA = 0.012 (< 0.05), CFI = 0.998 (> 0.9), TLI = 0.996 (> 0.9), and SRMR = 0.026 (< 0.05).